Controle acionário compartilhado e solução de impasses: estudo de caso da Companhia Brasileira de Distribuição - Neves, Lara Britto de Almeida Domingues (2016)
This master's thesis aims at investigating the corporate shared control, specifically about potential deadlocks in corporate decisions that might occur due to the corporation’s share distribution structure, it’s organizational structure, or contractual arrangements undertaken by parties. The approach to the subject comes from the study of a real case (the case of the Companhia Brasileira de Distribuição). The research starts with the systematization of case data, a critical assessment of how the Company control shared between Abilio Diniz group and Casino group was structured, in 2005, from the point of view of form and content. The study aims to extract lessons, with generalization potential, on mechanisms for breaking deadlock where business dispute has arisen because there is no consensus in decision making. Part I is descriptive, and aims to make the reader aware of the context of the negotiation transactions and the proposal of shared control by the major shareholders, that was concentrated in two agreements: a 'joint venture agreement' and a 'shareholder’s agreement'. Part II has an analytical purpose and seeks to compare actual data vis-a-vis theoretical positions as it is found in the legal literature.